Implementasi Digitalisasi Pelayanan Publik untuk Meningkatkan Akuntabilitas Pemerintah di Kota Gorontalo - Serlin Ahmad; Udin Hamim; Dwi Indah Yuliani Solihin (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
This study examines the implementation of public service digitalization to improve government accountability in Limba U1 Village, Gorontalo City, as part of broader efforts to enhance the quality of administrative services in the digital era. Despite increasing initiatives toward digital transformation, local governance continues to face challenges in infrastructure, human resource capability, and community engagement. The research aims to analyze how digitalization enhances administrative efficiency and strengthens transparency within local government operations. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving local officials and community members. The findings indicate that digitalization improves service delivery speed, data transparency, and bureaucratic accountability, while also exposing barriers related to limited technical capacity and uneven digital literacy among both staff and citizens. The study concludes that effective digital governance requires strong leadership commitment, capacity building, and inclusive public participation. Furthermore, this research provides empirical insight into the local adaptation of national digital policies within the Electronic-Based Government System (SPBE) framework, emphasizing that successful digital transformation depends on institutional readiness and community involvement. Leadership consistency and interagency coordination are also identified as critical factors for ensuring the sustainability of digital initiatives. By linking technological innovation with social inclusion and bureaucratic reform, this study underscores that digitalization should not be viewed merely as a technical adjustment but as a form of institutional transformation toward accountable and citizen-oriented governance, offering strategic implications for strengthening the capacity and responsiveness of local public institutions in Indonesia.